Typification and taxonomic remarks in Petrosedum (Crassulaceae) - Gallo, Lorenzo (Phytotaxa, 2020)
Within the genus Petrosedum Grulich (1984: 39), as already previously stated (Gallo 2017: 208), some names still lack of a typification, and in view of a review of this genus, it seems appropriate to fill this gap. Four names are concerned here: S. amplexicaule, S. montanum, S. pruinatum and S. tenuifolium. Herbarium acronyms follow Thiers (2020+).